The Hindwings of Ants: A Phylogenetic Analysis - Cantone, Stefano [UNESP]; Von Zuben, Claudio Jose [UNESP] (Hindawi Ltd, 2019)
In this study, we compare and analyze different ant taxa hindwing morphologies with phylogenetic hypotheses of the Family Formicidae (Hymenoptera). The hindwings are classified into three Typologies based on progressive veins reduction. This analysis follows a revision of the hindwing morphology in 291 extant and eight fossil genera. The distribution of different Typologies was analyzed in the two Clades: Formicoid and Poneroid. The results show a different distribution of Typologies, with a higher genera percentage of hindwings of Typology I in the Clade Poneroid. A further analysis, based on genetic affinities, was performed by dividing the Clades into Subclades, showing a constant presence of hindwings of Typology I in almost all the Subclades, albeit with a different percentage. The presence of hindwings of Typology I (hypothesized as more ancestral) in the Subclades, indicates the genera that could be morphologically more similar to their ancestral ones. This study represents the first revision of the ants' hindwings, showing an overview of the distribution of different Typologies.